2000
DOI: 10.1006/jabr.1999.8081
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Results for Primitive Permutation Groups and Irreducible Linear Groups

Abstract: A well-developed branch of asymptotic group theory studies the properties of classes of linear and permutation groups as functions of their degree. We refer to the surveys of Cameron [4] and Pyber [17,18] and the recent paper by Pyber and Shalev [19] for a detailed exposition of this subject. In this paper we concentrate our attention on the number of generators. Our results, like most recent results in this area, depend on the classification of finite simple groups (which will be referred to hereafter as CFSG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…By [34], if G is a primitive permutation group of degree n > 2, then there is a constant a such that d(G) ≤ a log n/ √ log log n. Now, applying Theorem 8.1, we obtain the desired result. Corollary 8.2 improves an n c log n bound which is the main result of [49].…”
Section: Corollary 82mentioning
confidence: 85%
“…By [34], if G is a primitive permutation group of degree n > 2, then there is a constant a such that d(G) ≤ a log n/ √ log log n. Now, applying Theorem 8.1, we obtain the desired result. Corollary 8.2 improves an n c log n bound which is the main result of [49].…”
Section: Corollary 82mentioning
confidence: 85%
“…McIver and Neumann [81] showed that every subgroup of S n can be generated by ⌊n/2⌋ elements if n = 3, and by 2 if n = 3. This bound is best possible for arbitrary subgroups, but for transitive or primitive subgroups it has been improved in [71,72] to the statements in the theorem. Now we are going to prove that the minimum number of generators of any 2-homogeneous finite group is 2.…”
Section: Group Theorymentioning
confidence: 99%
“…Theorem 6.5. ( [27]) Let G ≤ S n be a primitive permutation group. Then the smallest number of elements needed to generate G is at most C log n √ log log n ,…”
Section: Problemsmentioning
confidence: 99%